Defining Outcomes for β-cell Replacement Therapy in the Treatment of Diabetes: A Consensus Report on the Igls Criteria From the IPITA/EPITA Opinion Leaders Workshop. Issue 9 (September 2018) - Rickels, Michael R.; Stock, Peter G.; de Koning, Eelco J.P.; Piemonti, Lorenzo; Pratschke, Johann; Alejandro, Rodolfo; Bellin, Melena D.; Berney, Thierry; Choudhary, Pratik; Johnson, Paul R.; Kandaswamy, Raja; Kay, Thomas W.H.; et al.
Abstract : Abstract: β-cell replacement therapy, available currently as pancreas or islet transplantation, has developed without a clear definition of graft functional and clinical outcomes. The International Pancreas and Islet Transplant Association and European Pancreas and Islet Transplantation Association held a workshop to develop consensus for an International Pancreas and Islet Transplant Association and European Pancreas and Islet Transplant Association Statement on the definition of function and failure of current and future forms of β-cell replacement therapy. There was consensus that β-cell replacement therapy could be considered as a treatment for β-cell failure, regardless of etiology and without requiring undetectable C-peptide, accompanied by glycemic instability with either problematic hypoglycemia or hyperglycemia. Glycemic control should be assessed at a minimum by glycated hemoglobin (HbA1c ) and the occurrence of severe hypoglycemia. Optimal β-cell graft function is defined by near-normal glycemic control (HbA1c ⩽6.5% [48 mmol/mol]) without severe hypoglycemia or requirement for insulin or other antihyperglycemic therapy, and with an increase over pretransplant measurement of C-peptide. Good β-cell graft function requires HbA1c less than 7.0% (53 mmol/mol) without severe hypoglycemia and with a significant (>50%) reduction in insulin requirements and restoration of clinically significant C-peptide production. Marginal β-cell graft function is defined by failure to achieve HbA1c less than 7.0% (53 mmol/mol), the occurrence of any severe hypoglycemia, or less than 50% reduction in insulin requirements when there is restoration of clinically significant C-peptide production documented by improvement in hypoglycemia awareness/severity, or glycemic variability/lability. A failed β-cell graft is defined by the absence of any evidence for clinically significant C-peptide production. Optimal and good function are considered successful clinical outcomes. Abstract : A new consensus statement proposes that successful islet and pancreas transplant function be categorized as either "optimal" or "good." Unsuccessful islet and pancreas transplant function can be categorized as "marginal" or "failed."